Small‐scale thermal upwellings under the northern East African Rift from S travel time tomography. Issue 10 (21st October 2016) - Civiero, Chiara; Goes, Saskia; Hammond, James O. S.; Fishwick, Stewart; Ahmed, Abdulhakim; Ayele, Atalay; Doubre, Cecile; Goitom, Berhe; Keir, Derek; Kendall, J. Michael; Leroy, Sylvie; Ogubazghi, Ghebrebrhan; et al.
Abstract: There is a long‐standing debate over how many and what types of plumes underlie the East African Rift and whether they do or do not drive its extension and consequent magmatism and seismicity. Here we present a new tomographic study of relative teleseismic S and SKS residuals that expands the resolution from previous regional studies below the northern East African Rift to image structure from the surface to the base of the transition zone. The images reveal two low‐velocity clusters, below Afar and west of the Main Ethiopian Rift, that extend throughout the upper mantle and comprise several smaller‐scale (about 100 km diameter), low‐velocity features. These structures support those of our recent P tomographic study below the region. The relative magnitude of S to P residuals is around 3.5, which is consistent with a predominantly thermal nature of the anomalies. The S and P velocity anomalies in the low‐velocity clusters can be explained by similar excess temperatures in the range of 100–200°C, consistent with temperatures inferred from other seismic, geochemical, and petrological studies. Somewhat stronger VS anomalies below Afar than west of the Main Ethiopian Rift may include an expression of volatiles and/or melt in this region. These results, together with a comparison with previous larger‐scale tomographic models, indicate that these structures are likely small‐scale upwellings with mild excess temperatures, rising from a regional thermal boundary layer at the base of the upper mantle. Key Points: S wave tomography shows multiple upper mantle upwellings below the northern East African Rift as previously proposed using P tomography Both S and P anomalies are consistent with a dominantly thermal signature of 100‐200° excess temperature The complex transition zone structure may well connect to lower mantle roots revealed in large‐scale tomography